Can Aromatherapy Make People Feel Better Throughout Exercise? - Kwon, Sungho (Int J Environ Res Public Health, 2020)
We analyzed participants’ feelings and arousal before, during, and after exercise as per whether they receive aromatherapy. Twenty university students who regularly took part in health exercises were selected through purposive sampling. Changes in feelings were measured through a 2D circumplex model and an in-depth interview. The effects on exercisers who received aromatherapy were more positive than for those who did not receive any treatment. Specifically, it induced positive feelings during exercise, reduced fatigue during exercise, and improved participants’ feelings during the recovery period. Aroma has a key influence on exercisers’ feelings, and it can positively influence exercise satisfaction and persistence.